2016
DOI: 10.1155/2016/2715718
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Mitigates Kidney Injury in High Fat Diet‐Induced Obese Mice

Abstract: Obesity is prevalent worldwide and is a major risk factor for the development and progression of kidney disease. Hydrogen sulfide (H2S) plays an important role in renal physiological and pathophysiological processes. However, whether H2S is able to mitigate kidney injury induced by obesity in mice remains unclear. In this study, we demonstrated that H2S significantly reduced the accumulation of lipids in the kidneys of high fat diet- (HFD-) induced obese mice. The results of hematoxylin and eosin, periodic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
(77 reference statements)
1
17
0
Order By: Relevance
“…H 2 S has recently been recognized as an endogenous gaseous signaling molecule, along with nitric oxide and carbon monoxide 8 10 , 15 , 28 . A growing body of evidence indicates that H 2 S plays important and complex roles in renal physiological and pathophysiological processes 11 , 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 S has recently been recognized as an endogenous gaseous signaling molecule, along with nitric oxide and carbon monoxide 8 10 , 15 , 28 . A growing body of evidence indicates that H 2 S plays important and complex roles in renal physiological and pathophysiological processes 11 , 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The extent of renal interstitial fibrosis (RIF) was scored from 0 to 3 as follows: 0 = absent, 1 = less than 25% of the area, 2 = 25–50% of the area, and 3 = more than 50% of the area. The RIF index was obtained by the following formula: RIF index = (0 ×  n 0 + 1 ×  n 1 + 2 ×  n 2 + 3 ×  n 3)/( n 0 +  n 1 +  n 2 +  n 3) × 100% 28 . All specimens were anonymized and evaluated in a blinded manner.…”
Section: Methodsmentioning
confidence: 99%
“…The rats were randomly divided into the following four groups, with six rats per group: control group, rats fed with standard chow; doxorubicin (DR) group, rats in which the DR-induced kidney injury model was established, rats fed with standard chow; DR+NF group, with the establishment of the DR-induced kidney injury model, fed with standard chow plus NF from week 3 onwards; HFD group, rats were fed with a diet containing 60% of its calories in fat. For comparison of the lipidemic status in the kidneys, an HFD was fed to prepare the obese animal model as a positive control in our design, which also presented kidney injury [ 50 ] in tubule-interstitial fibrosis [ 51 ], lysosomal dysfunction and lipotoxicity [ 30 ], glomerulonephropathy, and proximal tubular damage [ 52 ]. To establish the DR-induced kidney injury model, a single injection of DR at a dose of 8.5 mg/kg was administered after weighting the rats.…”
Section: Methodsmentioning
confidence: 99%
“…To date, no pharmacological therapeutic has been developed to simultaneously target both the failing heart and the injured kidney. Previous studies have reported that H 2 S therapies effectively ameliorated renal dysfunction in several animal models of kidney diseases through differential mechanisms, suggesting that H 2 S-based therapies may be efficacious in treating both the heart and the kidney in HF 14, 38, 41, 42, 43, 44, 45, 46, 47. In consistent with previous literature, we observed that the mice received Control developed type-II cardiorenal syndrome as evidenced by elevated levels of plasma creatinine and renal fibrosis at 18 weeks post TAC (39).…”
Section: Discussionmentioning
confidence: 99%